Activating transcription factor 1 promoted migration and invasion in lung cancer cells through regulating EGFR and MMP‐2. Issue 10 (16th August 2019) - Cui, Jinggang; Yin, Zhaofang; Liu, Guohua; Chen, Xiaojun; Gao, Xiaolai; Lu, Huiling; Li, Wei; Lin, Dang
Abstract: Lung cancer is among the most frequently occurring cancers and the leading cause of cancer‐related deaths worldwide. Nonsmall cell lung cancer is accountable for 85% to 90% of all lung cancer cases and develops distant metastases with high mortality. In this work, we elucidated the role of activating transcription factor 1 (ATF1) in migration and invasion of lung cancer cells. We found that the migration and invasion were inhibited with ATF1 silencing in lung cancer cells. By contrast, ATF1 overexpression led to promotion in migration and invasion. The alteration in ATF1 expression induced a change in the epidermal growth factor receptor (EGFR) and matrix metalloproteinases (MMP)‐2 expression level in the same tendency. Thus, we provided a potential new candidate for therapies against lung cancer, showing the possible mechanism underlying the invasion and migration of lung cancer cells.